Peer assessment in modeling foreign language writing instruction - Aituganova K.K.; Eskazinova Zh.A. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2026)
The practice of teaching written speech in a foreign language to language arts majors through peer evaluation is examined in this article. The study's goal is to create a teaching model that incorporates peer evaluation into the framework for improving written speaking proficiency. This activity is practically significant because it fosters text analysis abilities, increases student autonomy, and develops critical thinking. In addition to discussing the pedagogical benefits and drawbacks of peer evaluation in language instruction, the essay outlines the modeling phases, research techniques, and model testing outcomes.
Keywords: learner autonomy; written speech; peer evaluation; modeling; language instruction; and proficiency in a foreign language